The Study Trees Potential for Forest in Universitas Lancang Kuning Pekanbaru - Marta Dinata; Fitridawati Fitridawati; Lusi Dwi Putri (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
The location of the study of Potential tree species for Peripheral Forest Development is determined by Lancang Kuning University, which is on Yos Sudarso road KM 8 Rumbai Pekanbaru, which is a fragmented habitat. The method used is census through measurement of area, structure observation, population enumeration, measurement of three dimensions. Calculating tree species diversity (H '), Assessing the suitability criteria of a type of tree for each type of green edge path area refers to the method of analyzing an integrated research plan, the important value index for the highest vegetation is acacia (Acacia auriculiformis) with a value amounting to 73.11. Acacia (Acacia auriculiformis) type of tree is less suitable. This is because the population is too high, where the debris that falls hard to decompose causes a thick pile when trampled slipperily and endangers safety, which eventually leaves litter accumulation causing soil conditions on the slopes to become soft because it is moist and has the potential to become landslides.